Mr. Buzz the Beeman - Ahlberg, Allan; Ill by Faith Jaques (London : Penguin, 1981)
Mr Buzz, his family, and all the neighbors chase a swarm of uncooperative bees through the countryside.
Keywords: Bees -- Fiction